Scaphoid Waist Internal Fixation for Fractures Trial (SWIFFT) protocol: a pragmatic multi-centre randomised controlled trial of cast treatment versus surgical fixation for the treatment of bi-cortical, minimally displaced fractures of the scaphoid waist in adults. Issue 1 (December 2016) - Dias, Joseph; Brealey, Stephen; Choudhary, Surabhi; Cook, Liz; Costa, Matthew; Fairhurst, Caroline; Hewitt, Catherine; Hodgson, Stephen; Jefferson, Laura; Jeyapalan, Kanagaratnam; Keding, Ada; Leighton, Paul; et al.
Abstract Background A scaphoid fracture is the most common type of carpal fracture affecting young active people. The optimal management of this fracture is uncertain. When treated with a cast, 88 to 90 % of these fractures unite; however, for the remaining 10-12 % the non-union almost invariably leads to arthritis. The alternative is surgery to fix the scaphoid with a screw at the outset. Methods/Design We will conduct a randomised controlled trial (RCT) of 438 adult patients with a "clear" and "bicortical" scaphoid waist fracture on plain radiographs to evaluate the clinical effectiveness and cost-effectiveness of plaster cast treatment (with fixation of those that fail to unite) versus early surgical fixation. The plaster cast treatment will be immobilisation in a below elbow cast for 6 to 10 weeks followed by mobilisation. If non-union is confirmed on plain radiographs and/or Computerised Tomogram at 6 to 12 weeks, then urgent surgical fixation will be performed. This is being compared with immediate surgical fixation with surgeons using their preferred technique and implant. These treatments will be undertaken in trauma units across the United Kingdom. The primary outcome and end-point will be the Patient Rated Wrist Evaluation (a patient self-reported assessment of wrist pain and function) at 52 weeks and also measured at 6, 12, 26 weeks and 5 years. Secondary outcomes include an assessment of radiological union of the fracture; quality of life; recovery of wrist range and strength; and complications. We will also qualitatively investigate patient experiences of their treatment. Discussion Scaphoid fractures are an important public health problem as they predominantly affect young active individuals in the more productive working years of their lives. Non-union, if untreated, can lead to arthritis which can disable patients at a very young age. There is a rapidly increasing trend for immediate surgical fixation of these fractures but there is insufficient evidence from existing RCTs to support this. The SWIFFT Trial is a rigorously designed and adequately powered study which aims to contribute to the evidence-base to inform clinical decisions for the treatment of this common fracture in adults. Trial registration The trial is registered with the International Standard Randomised Controlled Trial Register (ISRCTN67901257 ). Date registration assigned was 13/02/2013.